(3fSNI cJGH CfTCg CHh ESMGb EHQGgje Hf gdjd GdUGHi YfO aJM HZOGO hEfgRGe GdCJQGc YfgGs - (3GdUGHjA , CHh ESMGb EHQGgje Hf gdGd Hf EHQGgje Hf RgQhf GdMQGfj GdUGHF,J (B384 (3g` s ((3eMeO Cejf GdYHGSi s)
(3ChdgG (B:s
(3CeG HYO aEf ddg bVGjG fGaPI hCbOGQ eGVjI ajgf GdfYe GdShGHZ hGdfbe GdOhGeZ aCeG GdfYe ajDJjgG YHGOg CLeYjf HGOjI Ke jLRi HgG GdTGcQjf s
(3BNQgG (B:s
(3hCheG Edi LGfH CHj GdZfGFe abHdJ jOg hQLdg hTcQJg hOYhJ dg Je GdLRA GdKGfi ef efTCg GdUGHi s
(3HgG fXGe GdJYbjHIs
(3fSNI ecQQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B124s
Keywords: (3GdCOHs